Ide Pluralistik dalam Pemberian Fatwa Perspektif Syihab al-Din al-Qarafi (626-684 H/1228-1285 M) - Suraji, Suraji (Al-Manahij: Jurnal Kajian Hukum Islam, 2011)
This article studies the thought of al-Qarafi who lived in (626-684 H/ 1228-1285 M) in al-Qarafah - Kairo, Eqypt about the pluralistic ideas in giving fatwa (legal opinion). Al-Qarafi’s pluralistic ideas in giving fatwa include several issues. First, if a fatwa is requested by someone or a community that is not affiliated or committed to (taqlid) imam maz\hab (a mazhab leader), mujtahid or a certain opinion, a mufti (a scholar who gives fatwa) has freedom to give fatwa based on law opinion of which he believes to have the most excellent fundamental law. In contrast, if the fatwa request is from someone or a certain community that has made a pledge, affiliated, or socially identified to a certain maz\hab or tend to a certain law, mufti serves as an agent to choose a law opinion that is suitable with their maz\hab, belief, and religious social identity. Second, for those who request fatwa (mustafti) who want to change to other maz\hab (intiqal) or the result of other ijtihad (ideas) that he believes, there are no hindrances for him and that he deserves to get fatwa in accordance to the maz\hab that he believes. Among the implications of al-Qarafi’s pluralistic ideas in giving fatwa on the development of thoughts of contemporary Islamic law is giving the pragmatism principle foundation in the application of law. The implementation of the al-Qarafi’s ideas is also meaningful in establishing maz\hab tolerance, creating respectful situation in facing different opinion, and making harmony in interaction among Moslems.